2020
DOI: 10.3390/plants9081042
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grafting in the Resistance of Tomato to Viruses

Abstract: Grafting is routinely implemented in modern agriculture to manage soilborne pathogens such as fungi, oomycetes, bacteria, and viruses of solanaceous crops in a sustainable and environmentally friendly approach. Some rootstock/scion combinations use specific genetic resistance mechanisms to impact also some foliar and airborne pathogens, including arthropod or contact-transmitted viruses. These approaches resulted in poor efficiency in the management of plant viruses with superior virulence such as the strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 100 publications
(130 reference statements)
1
13
0
Order By: Relevance
“…AP2/ERF is the second largest family of TFs in the plants (Nakano et al, 2006). Quite similar to our findings, Spano et al (2020) reported upregulated AP2/ERF and xyloglucan hydrolase in the self-grafted tomato plants. The abovementioned results of the transcriptional analysis of the grafted watermelon seedlings might provide an understanding of the interactions between the ERF genes and ethylene-dependent mechanisms during the healing process of watermelon grafted on interspecific squash.…”
Section: Discussionsupporting
confidence: 91%
“…AP2/ERF is the second largest family of TFs in the plants (Nakano et al, 2006). Quite similar to our findings, Spano et al (2020) reported upregulated AP2/ERF and xyloglucan hydrolase in the self-grafted tomato plants. The abovementioned results of the transcriptional analysis of the grafted watermelon seedlings might provide an understanding of the interactions between the ERF genes and ethylene-dependent mechanisms during the healing process of watermelon grafted on interspecific squash.…”
Section: Discussionsupporting
confidence: 91%
“…Grafting is an ancient technique used to propagate plants vegetatively by combining desirable agronomic traits of the rootstock with those of the scion. It has been used in several plant species targeting a wide spectrum of traits, for instance, resistance to pathogens ( Boughalleb et al, 2007 ; Rivard and Louws, 2008 ; Spanò et al, 2020 ); tolerance to abiotic stress factors, such as water deficit, ( Liu et al, 2016 ), heavy metals ( Rouphael et al, 2008 ), and salinity ( Yanyan et al, 2018 ; Suárez-Hernández et al, 2019 ); improved fruit quality ( Davis and Perkins-Veazie, 2005 ); higher yields ( Cardinal et al, 2007 ); and architectural changes in scions ( Eltayb et al, 2014 ). However, breeding rootstocks for tree crops is slower than scion breeding for the same species.…”
Section: Introductionmentioning
confidence: 99%
“…As the use of grafted seedlings has increased in response to various stressors, the domestic seedling market is developing into specialized seedling production facilities with expertise in facility gardening, smart farms, and grafting machines ( Kwack et al, 2021 ). The development of the seedling industry reflects various cultivation management objectives, such as of soil-borne diseases in the growing environment, climate change, and increases in fruit production ( Rahmatian et al, 2014 ; Spanò et al, 2020 ). Furthermore, seedling industries have been used small container (plug tray having different sizes) for the efficient production of seedlings as it occupies small space and cost effective.…”
Section: Introductionmentioning
confidence: 99%